Prospective financial analysis with regard to enterprise risk exposure – the advantages of the Monte Carlo method - Kaczmarzyk, Jan (Prospektywna analiza finansowa z uwzględnieniem ryzyka przedsiębiorstwa – zalety podejścia Monte Carlo, 2016)
Prospective financial analysis is a key decision tool in an enterprise. The traditional approach confronts the forecasted value of a financial category or a financial ratio with a requirement or a standard. Knowing that the particular category or the ratio meets the requirement or the standard is a kind of risk information, but realizing that the requirement or the standard is met with a particular probability level is a detailed image of risk. The aim of the paper is to indicate the possibility to increase the effectiveness of prospective financial analysis by using a Monte Carlo simulation. The biggest advantage of the presented approach (that is in fact the evolution of the traditional scenario approach to risk analysis) is that it delivers the detailed probability distributions of key financial categories and ratios. Shareholders accepting the results of prospective financial analysis with the Monte Carlo simulation should accept risk in a more conscious way than in the case of the traditional approach
Nauki o Finansach = Financial Sciences, 2016, Nr 2 (27), s. 23-37
Keywords: corporate finance; financial analysis; risk; Monte Carlo; forecasting; finanse przedsiębiorstwa; analiza finansowa; ryzyko; prognozowanie